Optimising locally available resources for nutrient management to improve banana productivity in the farming systems in Rombo District, Kilimanjaro region - Rutazaha, J.E. (Sokoine University of Agriculture, 2019)
Banana is an important staple food in East Africa and an essential cash crop in the national and local economies. In Kagera and Kilimanjaro regions of Tanzania, banana is cultivated by more than 70% of smallholder farmers as a staple food in home gardens ranging from 0.5 to 2 hectares. Decline in banana yield has been reported in banana farming systems as a result of abiotic constraints (nutrient deficiencies and drought stress) and biotic constraints (pests and diseases). Decline in soil fertility and the ensuing nutrient deficiencies are among the major causes of the decline in banana yield. In the banana farming systems, nutrient removal most times exceeds their input, along with years of continuous cultivation results into negative yield trends. Most smallholder farmers are resource-constrained and thus limited in use of inorganic fertiliser due to cost, availability and usage. In this study the aim was to evaluate soil nutrient factors that affect banana production in order to identify localized soil nutrient management practices tailored to the biophysical and socioeconomic conditions of the smallholder farmer improve crop productivity. In evaluating soil fertility status in the banana farming systems, adequate indicators were employed, namely, physico-chemical and nutrient analysis, spatial analysis, crop yield and critical nutrient levels, limiting nutrients and nutrient balances. A survey approach was employed, involving sample collection in farmers’ banana fields. Using the Probability Sampling Technique, six wards (namely: Aleni, Mamsera, Manda, Mengeni, Mengwe and Shimbi) were selected in a systematic random manner based on banana production areas. Then from the six wards, a total of 100 sites were selected in a stratified random manner and geo-referenced. Allometric measurements, namely: girth at base (Gbase), girth at 1-m height (G1m), number of hands, and number of banana fingers on the bottom row of the second last hand were taken from among three selected mats with a